Harmonic Structure of Lower Hybrid Waves Driven by Energetic Ions at 4000 km Altitude: PIC Simulation. Issue 5 (2nd March 2023) - Kotani, T.; Toida, M.; Moritaka, T.; Taguchi, S.
Abstract: Past satellite observations in the polar region at about 4, 000 km altitude have reported lower hybrid waves (LHWs) and their harmonics, but the excitation mechanism of the harmonic LHWs has not yet been clarified. We perform one‐dimensional, electromagnetic, full particle‐in‐cell simulations by setting parameter values in the ranges observed by the satellite. The results from the two runs, that is, for ω pe /Ω e  = 0.1 and 0.2, show that the energetic ions can generate the harmonic LHWs in both cases. However, in the former case, more harmonic LHWs with larger amplitudes are created and stronger background‐ion acceleration is observed. Thus, our present simulations have solved a previously unsolved problem, revealing the possibility that harmonic LHWs are involved in ion acceleration phenomena commonly observed in the polar region, such as ion outflow. Plain Language Summary: The lower hybrid waves (LHWs), which can be excited by high‐energy ions with an anisotropic velocity distribution, are often observed in the polar region of the Earth's magnetosphere. Recently, increasing attention has been paid to the harmonics of the LHWs, which have been occasionally reported in the Earth's magnetosphere, but their excitation mechanism remains unclear. In this letter, we perform one‐dimensional, electromagnetic, particle‐in‐cell simulations to investigate the development of the LHWs and their harmonic waves. The simulations are based on the observation of harmonic LHWs in the polar region of the Earth's magnetosphere. We have demonstrated that high‐energy ions with a ring‐like velocity distribution can generate the LHWs and their harmonic waves, and background ions are strongly accelerated when harmonic LHWs are strongly excited. Thus, our simulations have solved a previously unsolved problem, revealing the possibility that the harmonic LHWs are involved in ion acceleration phenomena commonly observed in the polar region, such as ion outflow. Key Points: The harmonic structure of lower hybrid waves (LHWs) was reported at 4, 000 km altitude in the polar region, but its excitation mechanism remains unclear We have demonstrated that ring‐like energetic ions can generate the harmonic structure of LHWs The ion acceleration can be strongly enhanced when the harmonic LHWs can be strongly excited